Seleção de áreas para implantação de estruturas de passagem de fauna através da avaliação da conectividade funcional da paisagem - Silveira, Patrícia Batista da (2022)
In the search for new habitats in a fragmented landscape, animals tend to follow paths through the most permeable matrices, known as least-cost paths (LCP). Some approaches consider the least-cost paths as the ecological corridors of a landscape, such as this study. However, during their movement through the landscape, animals are faced with linear anthropic barriers that restrict their movements, such as highways and railroads. The wildlife crossings structures then appear in this context as punctual elements artificially installed in the landscape, in places where these road barriers exist, to restore or increase the biological flow and connectivity in that region. But what is verified in the great majority of cases is the installation of these structures of wildlife crossings just as a late remediation, only in some places where high numbers of road kills of wild animals are checked. This study presents a methodology for the prior identification of sites for the installation of structures for wildlife crossings, as part of the sustainable road planning of a landscape, through the joint analysis of the ecological corridors of animals (LCP) and road structures in a region. The area selected for this study was a geopolitical unit located in the Serra da Mantiqueira, in the Atlantic Forest domain, in the State of São Paulo, Brazil. Forty-four points were identified in the study area that demand the installation of wildlife crossings and/or other mitigation measures for fauna accidents. This study also questions the use of high resistance values for highways and railroads in ecological corridor softwares (for the LCP mappings), and suggests a different approach in the tabulation of the resistances of these road structures, with the use of lower values for these structures, for the identification of the true paths of fauna movement in a landscape - and consequently, the location of the real points where the implementations of wildlife crossings will be needed.